Pathophysiological Implications of Different Bicuspid Aortic Valve Configurations - F. A. Kari; F. Beyersdorf; M. Siepe (Cardiology Research and Practice)
There are numerous types of bicuspid aortic valve (BAV) configurations. Recent findings suggest that various BAV types represent different pathophysiological substrates on the aortic media level. Data imply that the BAV type is probably not related to location and extent of the aneurysm. However, BAV type is likely linked to the severity of aortic media disease. Some BAVs with raphe seem more aggressive than BAV without a raphe. Cusp fusion pattern, altered hemodynamics, and the qualitative severity of the disease in the aortic media might on the one hand share the same substrate. On the other hand, the aortopathy's longitudinal extent and location may represent a different pathophysiological substrate, probably dictated by the heritable aspects of BAV disease. The exact nature of the relation between BAV type and the aneurysm's location and extent as well as to the risk of aortic complications remains unclear. This paper reviews results of recent human and experimental studies on the significance of BAV types for local aortic media disease and location and extent of the aortopathy. We describe the known and hypothesized hemodynamic and hereditary factors that may result in aortic aneurysm formation in BAV patients.